Raziskovalni vodnik - Strnad, Simona; Novak, Darja (2020)
Guide to Research. Presentation of the organisation and activities of institutes, laboratories and centres of the Faculty of Mechanical Engineering
Keywords: Faculty of Mechanical Engineering; Promotion; Institutes; Laboratories; Reserach Centers; Research and Development; Cooperation with Industry